Perpindahan Panas Fiber Roof Building Kelapa Sawit (Elaeis Guineensis Jacq.) - Istianto Budhi Rahardja (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
Palm oil fiber are waste produce of a plant oil palm shaped splinters, solids, in length 3 – 4 cm , that is in the mesocarp of palm oil. Fiber knowing building is the result utilization of waste palm oil fiber as the roof of the building which used to quell heat of sunlight or from the heat source, so he could not directly exposed to to the people and surrounding environment. Fiber knowing building made by putting together fiber in in a mold and arranged with to dimension to be made. To bind between fiber, be used resin that has been in have get mixed material a catalyst so easy to dry quickly .The comparison between resin by fiber is 1: ¼. The results of the testing of heat conduction of the displacement that has been carried out on a body fiber test able to reduce heat the highest as much as 125°C and the lowest is 109°C from a source of heat is imparted much as 200°C. This shows that palm oil fiber can be used as an ingredient of the damper of heat to of building.